Effectiveness of vedolizumab and ustekinumab as second biologic agent in achieving target outcomes in tumor necrosis factor antagonists experienced patients with inflammatory bowel disease (enroll-ex study) - Alrashed, Fatema; Abdullah, Israa; Alfadhli, Ahmad; Shehab, Mohammad (Frontiers in Pharmacology, 2023)
Background: About a third of patients with inflammatory bowel disease (IBD) do not respond to anti-tumor necrosis factor (anti-TNF) therapy. In our study, we evaluated the effectiveness of vedolizumab and ustekinumab in achieving clinical and endoscopic outcomes in anti-TNF-experienced patients with IBD. Methods: We conducted a retrospective cohort study. Electronic medical records of patients with moderate to severe IBD, who were previously received anti-TNF therapies, were reviewed and evaluated retrospectively in a gastroenterology center. Outcomes of patients treated with ustekinumab or vedolizumab after failing one anti-TNF agent were evaluated. The primary outcomes were the percentage of hospitalization, surgery, mucosal healing and steroid-free remission. Mucosal healing was defined as a Mayo endoscopic score of 0 or 1 in ulcerative colitis (UC) and an SES-CD score of less than 3 in Crohn’s disease (CD). Outcomes were quantified using descriptive analysis. Results: A total of 207 (130 CD: 77 UC) patients with IBD who had previously received one anti-TNF agent were included in the study. Of the total cohort, 62 (30.0%) patients were receiving vedolizumab, and 145 (70.0%) patients were on ustekinumab. 101 (77.6%) patients with CD who failed one anti-TNF therapy were on ustekinumab. Of these patients, 26 (19.7%) patients were hospitalized, and 12 (11.9%) patients had IBD-related surgery. 16 (16.1%) patients had at least one corticosteroid course. 60 (59.0%) patients with CD on ustekinumab achieved mucosal healing. 29 (22.3%) patients with CD who failed one anti-TNF therapy were receiving vedolizumab. Of those, 7 (25%) patients were hospitalized, and 11 (37.9%) patients had IBD-related surgery. 15 (51.0%) patients achieved mucosal healing. 44 (57.1%) patients with UC who failed one anti-TNF therapy were on ustekinumab. Of these 6 (14.1%) patients were hospitalized, 3 (7.0%) patients had IBD-related surgery and 13 (30%) patients had at least 1 corticosteroid course. 25 (57.0%) patients achieved mucosal healing. 33 (42.8%) patients with UC who failed one anti-TNF therapy were receiving vedolizumab. Of those, 6 (18.6%) patients were hospitalized, and 16 (49.6%) patients had at least 1 corticosteroid course. 17 (53.2%) patients achieved mucosal healing. Conclusion: Ustekinumab and vedolizumab were both effective in achieving clinical outcomes in patients with IBD after failing an anti-TNF agent. However, patients receiving ustekinumab had numerically higher percentages of reaching target outcomes than patients receiving vedolizumab. A prospective head-to-head trial is warranted to confirm these findings.